2019
DOI: 10.1080/17453674.2019.1574387
|View full text |Cite
|
Sign up to set email alerts
|

The design of the cemented stem influences the risk of Vancouver type B fractures, but not of type C: an analysis of 82,837 Lubinus SPII and Exeter Polished stems

Abstract: Background and purpose — In total hip replacements, stem design may affect the occurrence of periprosthetic femoral fracture. We studied risk factors for fractures around and distal to the 2 most used cemented femoral stems in Sweden. Patients and methods — This is a register study including all standard primary Lubinus SPII and Exeter Polished stems operated in Sweden between 2001 and 2009. The outcome was any kind of reoperation due to fracture around (Vancouver type B) or distal to the stem (Vanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 34 publications
3
44
0
2
Order By: Relevance
“…An underreporting of reoperations due to PPFs may be present in this register-based study, maybe especially in those cases where the prosthesis is retained and the fracture is treated with osteosynthesis, as are most of the Vancouver C fractures. A recent large register study from the Swedish Hip Arthroplasty Register on THAs found a ten times higher risk of Vancouver B fractures but no statistical difference for Vancouver C fractures between the anatomic Lubinus SP2 and polished tapered Exeter stem(132). This study supports the notion that underreporting of Vancouver C fractures would probably not affect the results in Paper III.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…An underreporting of reoperations due to PPFs may be present in this register-based study, maybe especially in those cases where the prosthesis is retained and the fracture is treated with osteosynthesis, as are most of the Vancouver C fractures. A recent large register study from the Swedish Hip Arthroplasty Register on THAs found a ten times higher risk of Vancouver B fractures but no statistical difference for Vancouver C fractures between the anatomic Lubinus SP2 and polished tapered Exeter stem(132). This study supports the notion that underreporting of Vancouver C fractures would probably not affect the results in Paper III.…”
supporting
confidence: 72%
“…A higher risk of fractures with uncemented stem fixation has been described in the literature (107,131). A recent large register study on THAs from the Swedish Hip Arthroplasty Register found 10 times higher risk of Vancouver B fractures but no statistical difference for Vancouver C fractures between an anatomic stem (Lubinus SP2) and a polished taper stem (Exeter) (132). The literature on how patients are affected following PPFs is sparse.…”
Section: Periprosthetic Fracture (Ppf)mentioning
confidence: 99%
“… 10 , 11 The relationship between gender and PFF risk is also inconsistently reported, with several studies showing a greater risk in women, 12 men 13 , 14 or no difference. 15 , 16 However, an association exists with stem fixation as men are at a higher risk of PFF with cemented stems and women at a higher risk with cementless stems. 8 The effect of increasing age is more pronounced in women which is likely the result of menopause-related osteoporosis.…”
Section: Risk Factorsmentioning
confidence: 99%
“… 11 , 12 , 17 Dorr type C femurs 18 have been associated with an increased PFF risk when using cementless stems. 11 Indications for primary THR other than osteoarthritis are associated with an increased PFF risk, 13 , 15 with the greatest risk in avascular necrosis and femoral neck fracture. 8 , 17 …”
Section: Risk Factorsmentioning
confidence: 99%
“…The Vancouver classi cation developed by Duncan and Masri [10] is the most widely used for guiding the surgeon in pre-operative planning [7,[11][12][13], and it has been developed into the Uni ed Classi cation System for Periprosthetic Fractures [14,15]. New patterns of fracture has also been described for PFF around a hip femoral stem, with different prevalence over uncemented or cemented stem and apparently over stem geometry [16][17][18][19][20][21]. Modi ed Vancouver classi cation and correspondent proposed treatment from Literature are shown in Tables 1 and 2, respectively.…”
Section: Introductionmentioning
confidence: 99%